A Chiral Supramolecular Polymer Membrane with no Chiral Substituents by Highly Selective Photocyclic Aromatization of a One‐Handed Helical Cis‐cisoidal Polyphenylacetylene. Issue 5 (3rd December 2014) - Liu, Lijia; Long, Qing; Aoki, Toshiki; Namikoshi, Takeshi; Abe, Yunosuke; Miyata, Mari; Teraguchi, Masahiro; Kaneko, Takashi; Wang, Yudan; Zhang, Chunhong
<x xml:space="preserve">Abstract</x> A one‐handed helical cis‐cisoidal polyphenylacetylene (P) is successfully synthesized by an asymmetric‐induced polymerization of a chiral‐substituted phenylacetylene having two hydroxymethyl groups. Quantitative photocyclic aromatization of P in a membrane‐state followed by in situ removal of the chiral substituents affords a one‐handed helical supramolecular polymer membrane of the corresponding cyclic trimer (T) with no chiral substituents. The original one‐handed helicity of the precursor P is successfully transmitted to the resulting supramolecular helicity of de‐T. Both the hydrogen bonds and the π–π stacking are thought to contribute to the retention of the chirality during the two‐step reaction in the membrane state. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>